O crédito rural promotor do desenvolvimento e o Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) - Rodrigues, Sandra Terto Sampaio (2013)
Credit is a necessary element to rural production and its concession allows the producer has access to quality inputs and production technologies that improve agricultural production. By encouraging the production, credit becomes part of governmental initiatives to eradicate poverty in rural areas, however, it is necessary that the state intervenes in the rural credit offered by official banks not directed only towards large and medium producers. Thus, the National Program for Strengthening family Agriculture (Pronaf) was created with the purpose of providing adequate credit to farmers. This paper studies the credit operations of the Pronaf verifying that the loans have been a inducing mechanism in the development of rural zones, analyzing changes in the field after its creation in a critical context, emphasizing developmental theories, training Brazilian rural zones and the effect of the credit. Pronaf has established itself as a public policy, with positive results in the banking inclusion of family farmers and agrarian reform settlements across the country, however, the methodology of its concession needs adjustments to achieve better results in the application and repayment of credits especially with regard to timely payment of loan agreements.